The Analysis of Citations to Turkey Source Forensic Medicine Articles Indexed in Science Citation Index Between 2000 and 2004 - Altun, Gürcan; Balcı, Yasemin (The Bulletin of Legal Medicine, 2010)
The number of citations of an article shows the contribution to science. With this aim, the number of citations in Scopus and Web of Science (WoS) databases of 86 articles that were published in journals covered by Science Citation Index/Ex-panded and impact factors of journals which have been published with the contribution of forensic medicine specialist and assistants between the years of 2000 and 2004 were investigated. The impact factors of the articles were calculated according to the number of citations in both databases. The impact factor for WoS of the articles covered by the study was 1.48. This value was found to be below the national average. This result can be explained with the relatively low impact factor in that the journals published the half of the articles. The impact factor of the publications was the highest in 2001 (Scopus: 3.18, WoS: 2.64), the lowest in 2004 (Scopus: 1, WoS: 0.78). The impact factor of the publications in 2004 was low, because there was relatively short time from the time of publication until the time of investigation and approximately half of the articles have been never cited in this period.Key words: Forensic medicine, Turkey-source forensic medicine articles, citation, impact factor
Keywords: forensic medicine; Turkey source forensic medicine articles; citation; impact factor